Venetoclax in Combination with Decitabine for Relapsed T-Cell Acute Lymphoblastic Leukemia after Allogeneic Hematopoietic Cell Transplant - Leena T. Rahmat; Anna Nguyen; Haifaa Abdulhaq; Sonam Prakash; Aaron C. Logan; Gabriel N. Mannis (Case Reports in Hematology)
Long-term disease-free survival in adults with T-cell acute lymphoblastic leukemia (T-ALL) remains poor, particularly after relapse, with few available salvage options. Preclinical data suggest that inhibition of the antiapoptotic protein BCL-2 (B-cell lymphoma 2) either alone or in combination with other agents, may be a unique therapeutic approach for the treatment of T-ALL. We present a case of a young male with T-ALL, relapsed after allogeneic hematopoietic stem cell transplant, who achieved a second complete remission following salvage therapy with combined venetoclax and decitabine. Assessment of measurable residual disease by next generation sequencing showed no evidence of residual disease of a sensitivity of 1 × 10−6. While the combination of venetoclax and hypomethylating agents has shown promise in the treatment of relapsed/refractory AML, and to our knowledge, this is the first report of this combination demonstrating clinical activity in relapsed/refractory T-ALL.